In situ coagulation of yttria‐stabilized zirconia ceramic with enhancement of green body via polyvinyl pyrrolidone crosslink. Issue 29 (6th January 2020) - Gan, Ke; Lu, Yuju; Wu, Jia‐Min; Zhang, Xiaoyan; Wang, Yali; Ren, Bo; Huo, Wenlong; Chen, Yugu; Yang, Jinlong
ABSTRACT: In situ coagulation for yttria‐stabilized zirconia (YSZ) suspension via polyvinyl pyrrolidone (PVP) crosslink is reported. PVP is used to prepare sterically stabilized YSZ suspension. Influence of PVP on the dispersion of YSZ suspension was investigated. It indicates that well disperse YSZ suspension with 0.3 wt % PVP can be prepared. Dimethyl sulfate (DMS) was added at 40 °C to coagulate the suspension after degassing. Influence of DMS content and coagulation temperature on coagulation process and properties of green bodies were investigated. It indicates that sufficiently high viscosity to coagulate the suspension is achieved with the addition of 1 vol % DMS at 60~80 °C. The coagulation mechanism is proposed that the YSZ suspension is destabilized by the self‐crosslink of PVP. Coagulated samples with the highest wet compressive strength of 6.34 MPa could be demolded without deformation by treating 50 vol % YSZ suspension at 60 °C. Dense YSZ ceramics with relative density above 99.1% and flexural strength of 920 ± 90 MPa had been prepared by this method sintered at 1450 °C for 3 h. © 2020 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48889. Abstract :